2018
DOI: 10.18203/issn.2454-5929.ijohns20182702
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology accuracy in diagnosis of thyroid lesions: a comparative study with histopathological examination of thyroid swellings

Abstract: <p class="abstract"><strong>Background:</strong> Thyroid enlargement, whether diffuse or in the form of a nodule, leads to a battery of investigations to be done. Fine needle aspiration cytology (FNAC) is usually the first line of investigation but the limitations of cytology are well recognized in the diagnosis of some thyroid malignancies, in particular it is not able to differentiate between follicular adenoma and carcinoma. We conducted a prospective study to assess the role of FNAC in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…In our study there was female preponderance with male to female ratioof 1:9.27which is similar to the study done by Dimple et al with male to female ratio being 1:9 [12]. Shivani et al also noted 86% females and 14% male, with male to female ratio being 1:6.14 [3]. Obaid et al and most of the other studies also showed female predominance [9].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study there was female preponderance with male to female ratioof 1:9.27which is similar to the study done by Dimple et al with male to female ratio being 1:9 [12]. Shivani et al also noted 86% females and 14% male, with male to female ratio being 1:6.14 [3]. Obaid et al and most of the other studies also showed female predominance [9].…”
Section: Discussionsupporting
confidence: 90%
“…The presentation of the thyroid gland disease is widely varied. The course of the treatment and follow up rests on the proper diagnosis of the disorder with specific investigations [3].…”
Section: Introductionmentioning
confidence: 99%